Ligand-dependent conformational changes in the progesterone receptor are necessary for events that follow DNA binding. - Allan, G F (1992)
Hormones and antihormones induce related, but distinct, conformational changes in the progesterone receptor [Allan, G. F., Leng, X., Tsai, S. Y., Weigel, N. L., Edwards, D. P., Tsai, M.-J. & O'Malley, B. W. (1992) J. Biol. Chem. 267, 19513-19520]. In both cases the conformational change precedes the dissociation of heat shock proteins and binding to DNA. We have now investigated the steps in hormone action which are dependent upon this conformational change. We show that in the absence of ligand, monoclonal antibodies directed against different regions of the progesterone receptor can induce high-affinity binding to its response element in vitro. This antibody-induced DNA binding is presumably facilitated by enhanced dimerization of receptor monomers. However, antibodies do not induce the hormone-specific conformational change in the progesterone receptor and do not induce in vitro transcription by the receptor. In contrast, the antiprogestin ZK98299, which inhibits receptor binding to DNA, fully induces the antihormone-specific conformational change. Thus, our data imply that steroids induce a conformational change in their receptors which is necessary for events subsequent to DNA binding, most likely for transactivation.